1986
DOI: 10.1042/bj2380931
|View full text |Cite
|
Sign up to set email alerts
|

The ability of salts to inhibit the reaction between periodate anions and ovotransferrin

Abstract: The reaction between periodate anions and apo-ovotransferrin results in the rapid abolition of the iron-binding ability of the protein and the loss of approximately 4 mol of tyrosine/mol of protein. The degree of inhibition exerted by a variety of salts on the rate of this reaction is found to be inconsistent with the lyotropic series and suggests the existence of a complex anion-binding site in the apoprotein. The existence of this site may explain the action of periodate anions on ovotransferrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Nanogels NG-1 and NG-2 were prepared by cross-linking Mac-1 and Mac-2 (Scheme ) with the addition of NaIO 4 to the system for inducing the reaction of phenol groups of tyrosine contained in the RAADyC motifs. In such a way, tyrosine was coupled to form 3′3-dityrosine for achieving the cross-linked networks. Both Mac-1 and NG-1 were stable in water and PBS buffer as well as under the experimental conditions. No change in appearance and morphologies was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Nanogels NG-1 and NG-2 were prepared by cross-linking Mac-1 and Mac-2 (Scheme ) with the addition of NaIO 4 to the system for inducing the reaction of phenol groups of tyrosine contained in the RAADyC motifs. In such a way, tyrosine was coupled to form 3′3-dityrosine for achieving the cross-linked networks. Both Mac-1 and NG-1 were stable in water and PBS buffer as well as under the experimental conditions. No change in appearance and morphologies was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment of P. carterae with Na periodate completely inhibited Fe uptake, although it had no effect on [ 14C]methylamine uptake or on H14C03 fixation (data not shown). Ma periodate is best known as a reagent for reacting with vicinal hydroxyls in glycoproteins and glycolipids (Keren et al 1986) but has also been shown to react with tyrosine in the binding site of transferrin (Hsuan 1986) and with hydroxamates (Emery and Neilands 1960). Diazobenzenesulfonate (DABS) pretreatment inhibited uptake by 60%.…”
Section: Inhibitors Of Fe Uptake-the Effects Onmentioning
confidence: 99%
“…7) show that CNBr had cut at methionine residues 411,468 and 563 and that the fragments 411-468 and 469-563 form a two-chain peptide, oxBCc (calculated Mr 6350 + 11990). Use ofifess stringent oxidation conditions than those described by Geoghegan et al (1980), Yamasaki et al (1982) and Penner et al (1983) still results in the complete abolition of iron-binding ability (Hsuan, 1986) and may decrease the number of methionine residues that are reported to be oxidized by the reaction conditions of previous workers (Yamasaki et al, 1982;Penner et al, 1983). The positions of tryptic peptides from fragments BCd and oxBCc (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…The mechanism of the periodate oxidation of ovotransferrin is not known, but as an alternative to a free-radical mechanism it is possible that periodate forms a Malapradian, cyclic, intermediate complex with two tyrosine residues, similar to that suggested by Kaiser & Weidman (1965) for the oxidation of catechols by periodate. The specificity of the ovotransferrin reaction would therefore be a consequence of the stereochemistry of the tyrosine ligands, possibly enhanced by the ability of proximal basic residues to bind complex anions (Hsuan, 1986). In this way the periodate anion can be termed an affinity reagent for the iron-binding sites of transferrins, and preliminary results from limited chemical and enzymic proteolysis experiments suggest that the corresponding N-terminal-domain tyrosine residues of apo-ovotransferrin (92 and 191) are also cross-linked by periodate oxidation (J. J. Hsuan, unpublished work).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation